Leverage and Company Size on Tax Avoidance In Manufacturing Companies Listed On The IDX In 2018-2021 - Nur Sandi Marsuni; Yulitasari Yulitasari; Lina Mariana (Jurnal Riset Perpajakan: Amnesty, 2023)
This study aims to analyze the effect of leverage and company size on tax avoidance. The independent variables used are leverage and company size. The dependent variable used is tax avoidance. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange (IDX) in the 2018-2021 period. The method of determining the sample used is purposive sampling method with a sampling technique using certain criteria, obtained 21 companies that meet the sample criteria in this study during the observation period of 3 consecutive years so that the total sample is 63. The method of analysis of this study uses multiple linear regression. The results of this study indicate that the Leverage variable has a significant positive effect on Tax Avoidance and Company Size has no significant effect on Tax Avoidance. Then simultaneously, the Leverage variable, and Firm Size have a significant effect on Tax Avoidance.